Fonthill Recovered A Cultural History - Dakers, Caroline (Comparative Literature and Culture, 2018)
Fonthill, in Wiltshire, is traditionally associated with the writer and collector William Beckford who built his Gothic fantasy house called Fonthill Abbey at the end of the eighteenth century. The collapse of the Abbey's tower in 1825 transformed the name Fonthill into a symbol for overarching ambition and folly, a sublime ruin. Fonthill is, however, much more than the story of one man's excesses. Beckford's Abbey is only one of several important houses to be built on the estate since the early sixteenth century, all of them eventually consumed by fire or deliberately demolished, and all of them oddly forgotten by historians. Little now remains: a tower, a stable block, a kitchen range, some dressed stone, an indentation in a field. Fonthill Recovered draws on histories of art and architecture, politics and economics to explore the rich cultural history of this famous Wiltshire estate. The first half of the book traces the occupation of Fonthill from the Bronze Age to the twenty-first century. Some of the owners surpassed Beckford in terms of their wealth, their collections, their political power and even, in one case, their sexual misdemeanours. They include Charles I's Chancellor of the Exchequer, and the richest commoner in the nineteenth century. The second half of the book consists of essays on specific topics, filling out such crucial areas as the complex history of the designed landscape, the sources of the Beckfords' wealth and their collections, and one essay that features the most recent appearance of the Abbey in a video game.